Management strategies and treatment results of pediatric choledochal malformations in the Nordic countries. Issue 1 (January 2020) - Hukkinen, Maria; Björnland, Kristin; Gatzinsky, Vladimir; Iber, Tarja; Johansen, Lars S.; Qvist, Niels; Stenström, Pernilla; Svensson, Jan F.; Pakarinen, Mikko P.
Abstract: Background: Incidence and long-term outcomes of choledochal malformations (CMs) in children remain unclear. Methods: Clinical characteristics, operative details, complications, and follow-up data were collected from eight pediatric surgical centers in Sweden, Norway, Denmark, and Finland, which also answered a questionnaire addressing management practices. Results: During 2000–2017, 126 pediatric CMs were diagnosed, corresponding an incidence of 1:37, 400. Diagnostic, treatment, and follow-up practices varied markedly. Of patients with complete clinical data (n = 119), 85% and 11% had type I and IV CMs and were managed by open hepaticojejunostomy at median age of 2.5 (interquartile range 0.46–5.8) years. Associated malformations were more common in fusiform and type IV (23%) than cystic CMs (8%, p = 0.043). Pancreaticobiliary maljunction was more frequently confirmed in patients presenting with pancreatitis (26% vs. 7%, p = 0.005) and with fusiform CMs (56% vs. 25%, p = 0.001). Cholangitis/pancreatitis episodes, occurring in 12% during postoperative follow-up of 4.0 (2.0–7.9) years, associated with longer surveillance (OR 1.32, 95% CI 1.13–1.54, p < 0.001). However, only two thirds of centers continued follow-up until adulthood. No malignancies were reported. Conclusions: CM incidence was higher than traditionally reported among Western populations. Although open hepaticojejunostomy carries good short-term outcomes, long-term morbidity is noteworthy. Standardized evidence-based management strategies and long-term follow-up are encouraged.